Feed backing: A Classroom Interaction Tool in Bachelor of Elementary Education (BEEd) Classes - Roldan Jr., Roberto (JPAIR Multidisciplinary Research, 2015)
During instruction, a communication starts when the teacher imparts knowledge to the students. When the students absorb the information, process it and give feedback, they undergo a communication process. The study aimed to determine the extent of usage of teacher's feedback in the classroom interactions among Bachelor of Elementary Education (BEEd) students to maximize learning. Frequency counts, frequency percentage, mean and simple correlation analysis were utilized as statistical tools. As a whole, verbal criticisms were often used in Fourth Year while it is sometimes used in the other three-year levels. In general, written feedback was often witnessed in Fourth Year while written response was sometimes observed in the other college levels. Teachers apply more verbal reactions in classroom interactions followed by written and non-verbal feedbacks. Age is significantly related to written opinions. Teachers who have more teaching experiences give more written feedbacks than teachers with less teaching experience. Hence, the type of feedback which was always used in classroom interaction as perceived by the students was written replies while the most often used feedback given by the teacher was verbal feedbacks. There is a significant relationship between the teacher's profile on age, gender, civil status, educational attainment, subject taught and the length of service and the extent of the use of feedback in classroom interactions.
Keywords: Education; rejoinders; classroom intervention; descriptive design; Abra; Philippines